2012
DOI: 10.1159/000341104
|View full text |Cite
|
Sign up to set email alerts
|

Complete and Sustained Objective Response per RECIST to Irvalec (PM02734) in Undifferentiated Large Cell Esophageal Adenocarcinoma: A Case Report and a Review of the Literature

Abstract: Undifferentiated large cell carcinoma is a rare entity in esophageal cancer and very few data are available in the literature on this uncommon histological subtype. We report a case of a 58-year-old Caucasian male previously treated with cisplatin/5-fluorouracil, docetaxel and carboplatin/plitidepsin who received treatment with a novel antitumor agent, Irvalec (PM02734), as fourth line. The patient received treatment from July 2006 to July 2009, a total of 49 cycles, at a dose of 2.4 mg/m2 as a 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In fact, although the current World Health Organization Classification of Tumours of the Digestive System recognizes esophageal undifferentiated carcinomas as a distinct entity, the clinical and pathologic features are not described [8]. Within the literature, studies characterizing these neoplasms have been isolated to large epidemiological studies with little gross and histologic information or individual case reports that lack correlative clinical data [6,7,912,24]. To the best of our knowledge, our study represents the largest clinicopathological description of esophageal undifferentiated carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although the current World Health Organization Classification of Tumours of the Digestive System recognizes esophageal undifferentiated carcinomas as a distinct entity, the clinical and pathologic features are not described [8]. Within the literature, studies characterizing these neoplasms have been isolated to large epidemiological studies with little gross and histologic information or individual case reports that lack correlative clinical data [6,7,912,24]. To the best of our knowledge, our study represents the largest clinicopathological description of esophageal undifferentiated carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elisidepsin has been found to have synergistic effects when combined with several different conventional chemotherapeutic agents and tyrosine kinase inhibitors in cell lines and mouse xenograft models most likely due to its unique mechanism of action [ 6 , 7 ]. In clinical trials, elisidepsin has been shown to have a low toxicity profile [ 8 , 9 , 10 , 11 ] and preliminary assessment of its clinical efficacy showed interesting results in different solid tumors [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%